The Portrait of Code-Mixing in High School Students’ Facebook Status in Surabaya - Anzaska, Lidwine; Himmawati, Dian Rivia (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2017)
Code-mixing has become a phenomenon of language. Recently, there has been a growing interest among high school students to use English words in daily Indonesian language conversation. Furthermore, they do not only use it to communicate verbally but also in written texts. The purpose of this study was to reveal the social factors influencing the high school students in Surabaya to use code-mixing in their Facebook status. The results of this study showed that code-mixing in Facebook status is caused by several social factors. The first factor was the participants in the conversation on Facebook, including the distance of relationship between the speaker and the addressee, the age of the addressee, and the background of the addressee in the conversation. Moreover, the factor of the bilingual and multilingual usage within the society in Surabaya also supports the phenomenon of codemixing. Ultimately, the interaction using code-mixing has become a common thing within the society in Surabaya.